The Social Justice Ramifications Of Narrowing The Legal Definition Of “Wife’ In Malaysian Civil Law - Siva Subramaniam, Mageswary; Mohd Yusof, Yusnita; Johari, Darina (2016)
The status of “wife” confers on a woman a legal standing in relation to her husband which accords on her certain legal rights. In the context of Malaysian civil law this includes the right to initiate a claim in tort for any injuries or loss suffered by her deceased husband arising from the negligence of another. Such a right is conferred under s.7of the Civil Law Act 1956. The Court of Appeal in a recent unanimous decision in Tan Siew Sen & Others v Nick Abu Dusuki Bin Hj Abu Hassan [Civil Appeal No.B-04-249-09/2014] has ruled, that in the context of Non- Muslim marriages, only registration will confer the status of “wife” for the purpose all civil actions and thereby has narrowed the legal definition of the term “wife” in Malaysian civil law. The ruling of the court has the effect extending the application and scope of the Law Reform (Marriage & Divorce) Act 1976 beyond the parameters. Objectives: The objective of this paper is to assess the social justice ramifications of narrowing the legal definition of “wife” for civil actions in Malaysia, with particular reference to the interpretation of s.7 of the Civil Law Act 1956 which is a statutory provision applicable to both Muslims and Non –Muslims alike. Methodology: Doctrinal legal research/qualitative. Conclusion: The narrow interpretation is contrary to legislative intent and will result is social injustice of its preamble and thereby judicially transforming the definition of the term “wife” in Malaysia.